Porcine Milk Oligosaccharides and Sialic Acid Concentrations Vary Throughout Lactation - Mudd, Austin T.; Salcedo, Jaime; Alexander, Lindsey S.; Johnson, Stacey K.; Getty, Caitlyn M.; Chichlowski, Maciej; Berg, Brian M.; Barile, Daniela; Dilger, Ryan N. (Frontiers in Nutrition, 2016)
Background: Milk oligosaccharides (OS) are bioactive components known to influence neonatal development. These compounds have specific physiological functions acting as prebiotics, immune system modulators, and enhancing intestine and brain development. Objectives: The pig is a commonly used model for studying human nutrition, and there is interest in characterizing and quantifying OS composition of porcine milk across lactation. In this study, we hypothesized that OS and sialic acid (SA) composition of porcine milk would be influenced by stage of lactation. Methods: Up to 250 ml of milk was collected from 7 sows at each of three time points: d 0 (colostrum), d 7-9 (mature), and d 17-19 (weaning). Colostrum was collected within 6 h of farrowing and three-day intervals were used for mature and weaning milk to ensure representative sampling. Milk samples were analyzed for OS profiles by Nano LC Chip QTOF MS, OS concentrations via HPAEC-PAD, and SA (total and free) was assessed by enzymatic reaction fluorescence detection. Results: Sixty unique OS were identified in porcine milk. Neutral OS were the most abundant at each lactation stage (69-81%), followed by acidic-sialylated OS (16-29%) and neutral-fucosylated OS (2-4%). As lactation progressed, acidic OS decreased (P < 0.05), whereas neutral-fucosylated and neutral OS increased (P < 0.05) throughout lactation. Six OS were present in all samples analyzed across lactation (LDFH-I, 2´-FL, LNFP-I, LNnH, 3-Hex, 3´-SL), while LDFT was present only in colostrum samples. Analysis of individual OS concentrations indicated differences (P < 0.05) between days 0 and 7. Conversely, between days 7 and 18, OS concentrations remained stable with only LNnH and LNDFH-I decreasing (P < 0.05) over this period. Analysis of free SA indicated a decrease (P < 0.05) as lactation progressed, while bound and total SA increased (P < 0.05) across lactation. Conclusions: The present data suggest that while porcine milk OS profiles and concentrations differ compared with human milk OS, porcine milk OS composition is closer to human rather than to bovine milk, mainly because of the increased proportion of fucosylation during lactation and the ability for pigs to synthetize OS found uniquely in human milk.